1998
DOI: 10.1287/orsc.9.4.454
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management Processes and International Joint Ventures

Abstract: The management and processing of organizational knowledge are increasingly being viewed as critical to organizational success. By exploring how firms access and exploit alliance-based knowledge, the authors provide evidence to support the argument that the firm is a dynamic system of processes involving different types of knowledge. Using data from a longitudinal study of North American-based joint ventures (JVs) between North American and Japanese firms, they address three related research questions: (1) what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
550
1
25

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 760 publications
(598 citation statements)
references
References 29 publications
5
550
1
25
Order By: Relevance
“…For instance, the effects of hands-on, extensive training; and direct forms of control on learning and a strong skills base in the region in which to do this are conspicuous in Nissera's efforts to transfer continuous improvement practices of team structure and team culture that encourage change in routines at the UK site. This is in line with Inkpen and Dinur's (1998) finding that attempts to integrate subsidiaries strategically, such as personnel transfers, provide the means of interacting and exchanging knowledge that makes it easier to put knowledge into practice.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For instance, the effects of hands-on, extensive training; and direct forms of control on learning and a strong skills base in the region in which to do this are conspicuous in Nissera's efforts to transfer continuous improvement practices of team structure and team culture that encourage change in routines at the UK site. This is in line with Inkpen and Dinur's (1998) finding that attempts to integrate subsidiaries strategically, such as personnel transfers, provide the means of interacting and exchanging knowledge that makes it easier to put knowledge into practice.…”
Section: Discussionsupporting
confidence: 80%
“…In comparison to those in Japan, work systems are considered to be of lower tacitness in the UK (Inkpen and Dinur, 1998). Furthermore, as loose associations, firms are unable to share risks, hence undertake mainly short-term and low-risk investments in fixed capital, R&D, and human resources development (Lane, 1998).…”
Section: Institutional Context Of Learningmentioning
confidence: 99%
“…Nonaka and colleagues' (Nonaka, 1994;Nonaka & Takeuchi, 1995) view the essence of knowledge creation as the conversion of tacit knowledge into explicit knowledge. From previous contributions (Grant, 1996;Huang & Newell, 2003;Inkpen & Dinur, 1998;Okhuysen & Eisenhardt, 2002;Tell, 2011), knowledge integration can be analyzed more broadly than the complementarity of tacit and explicit knowledge, reflecting more of an institutionalization process.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from knowledge-based view (KBV) perspective have acknowledged that MNCs tend to be more protective of their advance technology, knowledge and competencies embodied in products, processes and management because these strategic valuable resources and competencies are their main sources of competitive advantage (Porter, 1985;Barney, 1991;Peteraf, 1993;Wernerfelt, 1984;Pralahad and Hamel). On the other hand, organizational learning (OL) perspective studies have suggested that technology and knowledge tend to be protected by the supplier when the recipients are opportunistic in the collaborative relationship (Inkpen, 1998a;Inkpen and Dinur, 1998;Child and Faulkner, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Since many studies on inter-firm TT are theoretical (Hamel, 1991;Inkpen, 1998a;Inkpen and Dinur, 1998) and have exclusively focused on a single or few dimensions of TT determinants (Pak and Park, 2004;Yin and Bao, 2006;Hau and Evangelista, 2007) there is a need for more hypothesis development and testing (Huber, 1991;Fiol, 1994). Based on a literature review, studies have shown that possibly there are no empirical studies on inter-firm TT and KT that have simultaneously examined the four TT characteristics: knowledge (KCHAR), technology recipient (TRCHAR), technology supplier (TSCHAR), and relationship (RCHAR) characteristics in a single model.…”
Section: Introductionmentioning
confidence: 99%